Integrating physician associates into the health workforce: barriers and facilitators. (2nd January 2019) - Szeto, Matthew CH; Till, Alex; McKimm, Judy
Abstract : Physician associates have been identified as a potential solution to the shortage of health-care workers in the UK, but the introduction of physician associates has not been universally welcomed and some uncertainty exists around their specific roles. This review enhances understanding of the barriers and facilitators for integrating physician associates into the workforce and identifies six key themes to inform future policy decisions at local and national levels.